Efektifitas Metode Pembelajaran Student-Centered Pada Masa Pandemi Covid-19 Di Universitas Aisyah Pringsewu. - Kurnia, Ulfa Isni; Latuny, Johannes (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2022)
The COVID-19 pandemic has disrupted the learning process in the classroom. Where the learning process must still be carried out but should not be gathered/busy. This makes the learning process change online. The learning process is still carried out online or in other words it is done online. To make the atmosphere of the online learning process active, educators can innovate in the learning process. One that can be used is the Student Centered Learning (SCL) method. Researchers see the effectiveness of the SCL learning method implemented in the online learning process. The research method used is a descriptive qualitative approach. The research subjects are students of Information Technology Education Study Program. The results of this study are that the SCL method has been applied well by the PTI study program, including changes in learning patterns in students, changes in teaching patterns, the occurrence of an interactive, active and dynamic learning atmosphere.